2006
DOI: 10.1186/1471-2458-6-166
|View full text |Cite
|
Sign up to set email alerts
|

Blood donors' motivation and attitude to non-remunerated blood donation in Lithuania

Abstract: Background: In the Soviet period, the blood donation system operated in Lithuania exclusively on a remunerative basis. After joining the EU, Lithuania committed itself to meeting the EU requirements to provide all consumers within its boundaries with safe blood products made from voluntary unpaid blood donations. However, the introduction of a non-remunerated donation system may considerably affect donors' motivation and retention. Thus the aim of the current research was to determine blood donation motives am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 15 publications
1
42
0
4
Order By: Relevance
“…Provided no remuneration were offered, 28.44% of the respondents would carry on doing it, 29.6% would do it only in an emergency, 29.6% would donate blood merely to their family or friends, and 12.3% would quit it completely. [17] In Greece, data on demographics, donation behaviour, incentives, risk perception and attitude towards donation and transfusion were analysed separately for volunteer and replacement donors and nondonors. The results showed that women and young people donate the least in Greece.…”
Section: Discussionmentioning
confidence: 99%
“…Provided no remuneration were offered, 28.44% of the respondents would carry on doing it, 29.6% would do it only in an emergency, 29.6% would donate blood merely to their family or friends, and 12.3% would quit it completely. [17] In Greece, data on demographics, donation behaviour, incentives, risk perception and attitude towards donation and transfusion were analysed separately for volunteer and replacement donors and nondonors. The results showed that women and young people donate the least in Greece.…”
Section: Discussionmentioning
confidence: 99%
“…The absolute majority of the paid donors (92%) think they should be offered a monetary compensation for blood donation, while more than half of the non-remunerated donors (55.9%) claimed they would be content with a mere appreciation of the act. About 28.4% of the respondents would carry on doing it, 29.6% would do it only in emergency, 29.6% would donate blood merely for their family or friend and 12.3% would quit it completely [17].…”
Section: Introductionmentioning
confidence: 99%
“…Motivation for blood donation has therefore been investigated in many countries (Allam and Masalmeh Bel 2004;Buciuniene et al 2006;Godin et al 2005;Sampath et al 2007). Blood banks in São Paulo, Brazil, have introduced donation policies and marketing campaigns to improve the quantity and safety of the blood supply.…”
Section: Introductionmentioning
confidence: 99%